Grzecznie po (staro)polsku? "Pogranicza" językowo-kulturowe gratulacji i życzeń we współczesnej polonijnej wspólnocie komunikatywnej na Ukrainie = Politely in (old) polish? Language-cultural "borderlands" of congratulations and wishes in contemporary polish communication community in Ukraine - Krawczuk, Ałła (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the article analyzes the types of interference the result of which is the formation of different contrasted with the Polish nationwide congratulations and expressing someone`s wishes structures in the language of the Polish community living in Ukraine. It was predicted the possible communicative "danger zones" caused by different types of interferencje: grammar, lexical-semantic, language-cultural.
Keywords: gratulacje; życzenia; interferencja; polszczyzna polonijna na Ukrainie; świadomość językowa; pogranicze; congratulations; wishes; interference; the Polish language of Polonia in Ukraine; language awareness; borderland